Effect of nebulised inhalation of antibiotics on preventing ventilator-associated pneumonia in critically ill patients: a systematic review and meta-analysis - Xin Liu; Sen Zhang; Yu Zhang; Qian Liu; Yuning Feng; Jun Wan; Xinyi Jiang; Xiang Yuan; Xian Chen; Qingyu Bao; Yihong Shen; Yongjie Deng; et al. (BMJ Open)
Objective To investigate whether prophylactic nebulised antibiotic inhalation reduces the incidence of ventilator-associated pneumonia (VAP) in critically ill adults undergoing mechanical ventilation.Study design Systematic review and meta-analysis of randomised controlled trials.Data sources PubMed, Embase and the Cochrane Central Register of Controlled Trials were searched from inception to 1 January 2024 without language restrictions.Eligibility criteria for selecting studies We included randomised controlled trials comparing prophylactic nebulised antibiotics with placebo or no treatment in mechanically ventilated adult intensive care unit (ICU) patients. Two independent reviewers conducted data extraction and assessed risk of bias. A meta-analysis was performed using random-effects models to calculate relative risks (RRs) for VAP and secondary outcomes.Results Of the 2663 studies screened, four were deemed suitable for analysis, involving a total of 1160 patients (574 receiving prophylactic antibiotics via nebulised inhalation). Nebulised antibiotics reduced the incidence of VAP compared with control (RR 0.70, 95% CI 0.52 to 0.93, I²=38%, low-certainty). There were no statistically significant differences in ICU mortality (RR 0.89, 95% CI 0.73 to 1.09, I²=0%, low-certainty, moderate-certainty) or hospital mortality (RR 0.93, 95% CI 0.78 to 1.11, I²=0%, moderate-certainty). Risk of bias varied across studies, with one trial assessed as high risk, one with some concerns and two with low risk.Conclusions Nebulised prophylactic antibiotics may reduce the incidence of VAP in critically ill patients receiving mechanical ventilation, though secondary outcomes did not differ between the intervention and control groups. The findings should be interpreted with caution due to the small number of included trials and low certainty of evidence.PROSPERO registration number CRD42024496276.